Analgesic activity of 4-amino-5-methyl-4H-1,2,4-triazol-3-thiones - T. V. Kravchenko; О. I. Panasenko; Ye. G. Knysh (Zaporozhye State Medical University, 2018)
Аbstract Significance. Nowadays non-steroidal anti-inflammatory drugs have found a wide application in treatment of medical conditions. Despite the clinical effectiveness of non-steroidal anti-inflammatory drugs, their administration is followed by a set of side effects. With aim to reveal the substances with a potency of altering pain threshold in animals, the action of 4-amino-5-methyl-4H-1,2,4-triazol-3-thiones on the nociceptive system in conditions of thermal irritation of rats' extremities was studied. Aim. Study of the analgesic activity of 4-amino-5-methyl-4H-1,2,4-triazol-3-thiones. Materials and methods. Analgesic activity of the synthesized compounds was evaluated in terms of the set of experiments conducted on white rats of 180-240 g weight. The primary pain threshold after the administration of the substances was assessed using a "hot plate" test, involving a metal plate heated at 55 oC as an irritator. The time of the corresponding response (paw licking, jumping out, squeaking) was measured in seconds. Analgesic activity was assessed by observations of the alterations of pain threshold of the group of studied animals to whom the substances of research were administrated, comparing results with the control group and expressing them in percent. Results. According to the results, it was concluded that the compound of 4-(3,4-dimethoxebenzylidenamino)-5-methyl-4H-1,2,4-triazol-3-thione was the most potent, which reduced the sensitivity to thermal irritation of extremities in the group of animals by 127.78%; that said, its activity is higher than that for the reference drug Analgin, which was also evaluated in a "hot plate" test. It was established that substance (IV) was slightly more active than the reference drug Analgin, demonstrating 121.11% of analgesic activity. Processing of the experimental data revealed some dependencies between the chemical structure and pharmacological activity of the substances of research. Conclusion. The obtained results demonstrate that analgesic activity is existent among the set of 1,2,4-triazole derivatives, which mandates a deeper research of the effectiveness and safety of the most active compounds among the studied compounds.